Landscape Plant Management in Pinge Tourism Village - Mahardika, Ida Bagus Komang; Rahman, Siti Maslizah Abdul; Sudewa, Ketut Agung; Udayana, I Gusti Bagus; Sukamadewi, Desak Ketut Tristiana; Astiari, Ni Komang Alit; Andriani, A. A. S. P. R. (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Tourist villages will need infrastructure that supports tourism activities such as places to eat, places to stay, rest areas, galleries, and so on, one of whose goals is to improve the living standards of local people. This causes the number of plant species to decrease. Plant conservation by utilizing local wisdom is one of the efforts to reduce the decline in the number of plant species. Balinese people need many types of plants to support their ceremonial activities. The application of Tri Hita Karana and Tri Mandala in the daily life of the Balinese people is expected to support plant conservation activities and support tourism activities and provide economic benefits in the Pinge traditional village. The concept of Tri Hita Karana derives from the concept of Tri Mandala which consists of the main mandala as a parahyangan or holy place, Madya mandala in the form of a yard which includes residential buildings and natah, while nista mandala yard in the form of the back house (teba) and the yard of the front house (telajakan). Traditional Balinese gardening uses the concept of Tri Mandala. The problems raised in this